Bipolar anodal septal pacing with direct LBB capture preserves physiological ventricular activation better than unipolar left bundle branch pacing - Curila, Karol; Jurak, Pavel; Prinzen, Frits; Jastrzebski, Marek; Waldauf, Petr; Halamek, Josef; Tothova, Marketa; Znojilova, Lucie; Smisek, Radovan; Kach, Jakub; Poviser, Lukas; Linkova, Hana; et al. (Frontiers in cardiovascular medicine, 2023)
BACKGROUND: Left bundle branch pacing (LBBP) produces delayed, unphysiological activation of the right ventricle. Using ultra-high-frequency electrocardiography (UHF-ECG), we explored how bipolar anodal septal pacing with direct LBB capture (aLBBP) affects the resultant ventricular depolarization pattern. METHODS: In patients with bradycardia, His bundle pacing (HBP), unipolar nonselective LBBP (nsLBBP), aLBBP, and right ventricular septal pacing (RVSP) were performed. Timing of local ventricular activation, in leads V1-V8, was displayed using UHF-ECG, and electrical dyssynchrony (e-DYS) was calculated as the difference between the first and last activation. Durations of local depolarizations were determined as the width of the UHF-QRS complex at 50% of its amplitude. RESULTS: aLBBP was feasible in 63 of 75 consecutive patients with successful nsLBBP. aLBBP significantly improved ventricular dyssynchrony (mean -9 ms; 95% CI (-12;-6) vs. -24 ms (-27;-21), ), p < 0.001) and shortened local depolarization durations in V1-V4 (mean differences -7 ms to -5 ms (-11;-1), p < 0.05) compared to nsLBBP. aLBBP resulted in e-DYS -9 ms (-12; -6) vs. e-DYS 10 ms (7;14), p < 0.001 during HBP. Local depolarization durations in V1-V2 during aLBBP were longer than HBP (differences 5-9 ms (1;14), p < 0.05, with local depolarization duration in V1 during aLBBP being the same as during RVSP (difference 2 ms (-2;6), p = 0.52). CONCLUSION: Although aLBBP improved ventricular synchrony and depolarization duration of the septum and RV compared to unipolar nsLBBP, the resultant ventricular depolarization was still less physiological than during HBP.
Keywords: dyssynchrony; anodal septal pacing; LBBP; ultra-high-frequency ECG; His bundle pacing